POLA KOMUNIKASI PENDAMPING DALAM PENINGKATAN PEMAHAMAN KELUARGA PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN TERHADAP PENGASUHAN DAN PENDIDIKAN ANAK - Herri Prasetyo (Jurnal Komunikasi dan Budaya, 2020)
Poverty has a very broad impact, one of which is the parents' ignorance of child care and education, this is caused because parents are busy with the demands of fulfilling the family's economy. The government through the social ministry is implementing a social protection program, the Family of Hope Program, where the government helps families that have been designated as participants in the form of conditional cash transfers, empowerment and assistance to break the poverty chain. The facilitator has a very important function in determining the success of this poverty alleviation program. The communication pattern applied by the facilitator also has a large percentage in an effort to increase the understanding of beneficiaries. This study seeks to see the communication patterns applied by the facilitator in improving the understanding of beneficiaries towards child care and education in the Keling Kebun Kelurahan in the city of Bengkulu based on the Joseph A Devito theory in which there are 5 communication patterns. This study uses qualitative methods with data collection techniques, participant observation, interviews and focus group discussions, and documentation studies. While data processing and analysis starts from the reduction of data found in the field, presents the data, and draws conclusions. The results of the study obtained that the companion in an effort to increase understanding of the care and education of beneficiary children that the communication pattern of all channels or star communication patterns is the most dominant. in this study found the fact that in keling orchards there was no increase in understanding of child care and education after empowerment through group meetings, this was because prior to the PKH program the community had already known and practiced ways of raising and educating good children .